Intersectionality and human rights law - Atrey, Shreya, 1988-; Dunne, Peter (Oxford, UK ; New York, NY : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This collection of essays analyses how the diversity in human identity and disadvantage affects the articulation, realisation, violation and enforcement of human rights. The question arises from the realisation that people, who are severally and severely disadvantaged because of their race, religion, gender, age, disability, sexual orientation, class etc, often find themselves at the margins of human rights; their condition seldom improved and sometimes even worsened by the rights discourse. How does one make sense of this relationship between the complexity of people's disadvantage and violation of their human rights? Does the human rights discourse, based on its universal and common values, have tools, methods or theories to capture and respond to the difference in people's lived experience of rights? Can intersectionality help in that quest? This book seeks to inaugurate this line of inquiry"--
Introduction : intersectionality from equality to human rights / Shreya Atrey -- Beyond universality : an intersectional justification of human rights / Shreya Atrey -- Harnessing the full potential of intersectionality theory in international human rights law : lessons from disabled children's right to education / Gauthier de Beco -- The potential and pitfalls of intersectionality in the context of social rights adjudication / Colm O'Cinneide -- The right to education and substantive equality : an intersectional reading / Sandra Fredman -- Class, intersectionality, the right to housing and the avoidable tragedy of Grenfell Tower / Geraldine Van Bueren QC -- Intersectionality, repeal, and reproductive rights in Ireland / Fiona de Londras -- The distance between us : sexual and reproductive health rights of rural women and girls / Meghan Campbell.
Includes bibliographical references and index.
Keywords: International law and human rights; Human rights -- Social aspects; Intersectionality (Sociology); International law and human rights; Human rights -- Social aspects; Intersectionality (Sociology)